Integration of Four Language Skills in Arabic Language Learning - Muflihah, Muflihah; Sholehan, Sholehan; Baihaqi, Muhammad (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2024)
This article discussed Arabic language learning integration skills in Arabic Language Education at UIN Sunan Ampel Surabaya. This research was a form of commitment to the quality of Arabic language education. Besides, it was prominent research to ensure the relevance of the curriculum and the effectiveness of Arabic language learning in the Arabic department at UIN Sunan Ampel. Moreover, this research aimed to improve educational programs and learning strategies that are more suitable to students' needs in facing the challenges of an increasingly complex era. A qualitative approach was used with observation, interviews and documentation with data sources from informants consisting of study program heads, school principals, Arabic teachers and PLP 2 program students as well as written documents related to the integration of four language skills in learning Arabic. The results of this research indicated that the comprehensive integration of the four language skills in the Arabic curriculum as stipulated in the madrasah independent curriculum provided significant potential for improving students' communication skills in Arabic as a global communication tool.